Complementary approaches to analyse genetic data in late onset Alzheimer's disease (LOAD) - Shi, Hui (2012)
Alzheimer's disease is the most common form (~60-80%) of dementia, currently affecting approximately half a million people in the UK and ~30 million people worldwide. The autosomal dominant form of AD represents a small proportion (~1-2%) of AD cases and is genetically well characterised. The vast majority of AD cases that show symptoms later in life (>65 years of age) are genetically complex. This type of AD, also known as late onset Alzheimer's disease (LOAD) disease, is still highly heritable with an estimated heritability of up to 76% (Gatz et al., 2006).